2014
DOI: 10.1016/j.biortech.2014.07.046
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study on supercritical water gasification of Laminaria hyperborea : A carbohydrate-rich macroalga

Abstract: The potential of supercritical water gasification (SCWG) of macroalgae for hydrogen and methane production has been investigated in view of the growing interest in a future macroalgae biorefinery concept. The compositions of syngas from the catalytic SCWG of Laminaria hyperborea under varying parameters including catalyst loading, feed concentration, hold time and temperature have been investigated. Their effects on gas yields, gasification efficiency and energy recovery are presented. Results show that the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 31 publications
(28 reference statements)
2
25
1
Order By: Relevance
“…The gas products obtained from the reactions were sampled via gas-tight plastic syringes and immediately analysed using gas chromatography [20,22]. Briefly, permanent gases including hydrogen, nitrogen and carbon monoxide were analysed using a column fitted on a GC with a thermal conductivity detector (GC-TCD).…”
Section: Gas Products Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The gas products obtained from the reactions were sampled via gas-tight plastic syringes and immediately analysed using gas chromatography [20,22]. Briefly, permanent gases including hydrogen, nitrogen and carbon monoxide were analysed using a column fitted on a GC with a thermal conductivity detector (GC-TCD).…”
Section: Gas Products Analysismentioning
confidence: 99%
“…They also showed that attempts to increase feed concentrations resulted in poor conversion difficulties due to tar formation, reactor pulling and clogging of the pump outlets during continuous operation. In addition, high biomass feedstock concentrations in batch reactors have resulted in low carbon gasification efficiencies and reduction in hydrogen yields [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, hydrothermal gasification has been seen as a good processing method for carbohydrate‐rich biomass, like macroalgae (Cherad et al . ).…”
Section: The Importance Of Chemical Composition Of Macroalgae In Biofmentioning
confidence: 97%
“…The use of macroalgae in the biofuel industry is still under development and even recent results on this topic are widely based on laboratory or meso-scale operations (Bastianoni et al 2008;Bruhn et al 2011;Maceiras et al 2011;Jang et al 2012;Wargacki et al 2012;Cherad et al 2014). This article provides information on the chemical composition of macroalgae in relation to the feasibility of using the different compounds for biofuel production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation